The story of filicide in Lam Yazra (barren) novel - Alimoradi, Zahra; Khalilollahi, Shahla (Opción, 2019)
The main issue of this research is to answer the question of how comparable are the myth of filicide in Shahnameh with this novel. This research has been analyzed with respect to its purpose, using library resources and descriptive and documentary method. As a conclusion, the novel that is part of the sacred defense literature, or is a kind of war literature and has been written in recent time, but has mythical and symbolic aspects that from the beginning draw the readers’ mind towards the story of Rostam and Esfandiar, with a verse from the story of Rostam and Sohrab